2019
DOI: 10.1111/1467-8454.12153
|View full text |Cite
|
Sign up to set email alerts
|

Credit card cash‐out as informal financing: Evidence from China

Abstract: Using a proprietary account-level database from a commercial bank in China, we document that credit card holders can ease their credit constraints through the practice of cash-out based on bogus transactions using credit cards. We find that such behaviour might be beneficial to both cardholders and banks. First, we find that a 1% increase in the cumulative number of credit card cash-out transactions lowers the probability of default by 9.59%. Second, for private businesses, a 1% increase in the number of abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…As documented by Bird et al (1999) and Collins et al (2015), economic cycles shape the pattern of credit card debt among low‐income households. As Chinese households are generally credit depressed, the emergence of credit cards has effectively alleviated cardholders' credit constraints (Ma et al, 2019). It is also found that liquidity constrained households use credit cards as an alternative financing source for their small business (Yuan et al, 2021), and the access to credit cards also stimulates entrepreneurship (Xu et al, 2022) through the liquidity enhancement channel.…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…As documented by Bird et al (1999) and Collins et al (2015), economic cycles shape the pattern of credit card debt among low‐income households. As Chinese households are generally credit depressed, the emergence of credit cards has effectively alleviated cardholders' credit constraints (Ma et al, 2019). It is also found that liquidity constrained households use credit cards as an alternative financing source for their small business (Yuan et al, 2021), and the access to credit cards also stimulates entrepreneurship (Xu et al, 2022) through the liquidity enhancement channel.…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%
“…For instance, credit cards have been shown to play an essential role in financing Chinese households' small businesses. Ma et al (2019) demonstrate the role of credit cards as an informal channel through illegal cash‐out practices in alleviating Chinese business households' credit constraints. Xu et al (2022) show that credit cards are an important financing tool for SMEs, which are in general credit depressed.…”
Section: Introductionmentioning
confidence: 99%